A comprehensive review of lines in ophthalmology – The posterior segment - M Vivek Nayak; Harsh Sharma; Jasneet Kalra; Apoorva Jain; Mahisha Virdiana; Aditi Rao; Sufyan Ibrahim; Yogish Subraya Kamath (Journal of Clinical Ophthalmology and Research)
There are many “lines” in ophthalmology. Most of these are eponymous signs used to describe various observed phenomena in ocular diseases, while some of them are normal anatomical landmarks. They are mostly named after the ophthalmologist or scientist who described them. Some of them have been termed “streaks,” and “striae” as well, but what is common among them is that they are linear or near linear in appearance. There is a need in ophthalmological literature for a centralized article that describes these lines with good images. Overall, the objective is to provide a snapshot on lines in ophthalmology for quick reference. Our methodology involved a thorough search on Google Search, Wikipedia, Google Scholar, and PubMed platforms. The reference sections of articles were used to broaden the search further. With this, an exhaustive list of “lines,” “streaks” and “striae” in ophthalmology, was arrived at. This article will give a comprehensive review of these “lines” in the posterior segment of the eye, as a continuation of our previous article on the anterior segment. Each line will be described on its eponymous origin, etiology, pathogenesis, clinical features, and management. The disease or pathology that some of these lines represent will also be briefly touched upon, as it is relevant for the article.